The relationship between religious/spiritual well-being, psychiatric symptoms and addictive behaviors among young adults during the COVID-19-pandemic - Vuzic, Xenia D.; Burkart, Pauline L.; Wenzl, Magdalena; Fuchshuber, Jürgen; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2022)
Background: It is becoming increasingly apparent that the COVID-19 pandemic not only poses risks to physical health, but that it also might lead to a global mental health crisis, making the exploration of protective factors for mental well-being highly relevant. The present study seeks to investigate religious/spiritual well-being (RSWB) as a potential protective factor with regard to psychiatric symptom burden and addictive behavior. Materials and Methods: The data was collected by conducting an online survey in the interim period between two national lockdowns with young adults (N = 306; age: 18-35) in Austria. The primary study variables were assessed through the Brief Symptom Inventory 18 (BSI-18; psychiatric symptom load), the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST; addictive behavior/addiction risk) and the Multidimensional Inventory for Religious/Spiritual Well-Being short version (MI-RSWB 12), with its sub-dimensions Hope (HO), Forgiveness (FO), General Religiosity (GR) and Connectedness (CO). Results: We observed HO and FO as substantial negative predictors of psychiatric symptom burden. With regard to addictive behavior, HO in particular but also GR seem to have a protective function. Furthermore, we found positive connections between CO, psychiatric symptom burden and addictive behavior. Conclusion: In line with our assumptions, HO, FO and to a minor extent GR were confirmed as negative predictors regarding psychiatric symptom burden or addictive behavior in young adults, coping with the psychological threat of Covid-19 pandemic. These dimensions might be further considered as potential resources in clinical treatment. However, the positive prediction of mental illness parameters by increased feelings of CO (e.g., to the universe) could also be interpreted as an expression of exhaustion and alienation from the real world.